2009
DOI: 10.1002/smj.775
|View full text |Cite
|
Sign up to set email alerts
|

Choice and performance of governance mechanisms: matching alliance governance to asset type

Abstract: Formal and relational governance mechanisms are used in strategic alliances to coordinate resources and mitigate the risk of opportunistic behavior. While recent work has shown that these approaches are not mutually exclusive, we understand little about when one approach is superior to the other. Using data on the governance choices and subsequent performance of alliances in the German telecommunications industry, we find that the optimal configuration of formal and relational governance mechanisms depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(131 citation statements)
references
References 116 publications
3
92
0
1
Order By: Relevance
“…Second, it highlights the importance of analysing separately tangible and intangible RSIs. Previous research by Hoetker and Mellewigt (2009) posed this issue by showing how each type of investment entails different hazards of opportunism and requires different governance structures. Our paper complements theirs by also highlighting the importance of taking into account the type of supplier investing in these specific assets.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it highlights the importance of analysing separately tangible and intangible RSIs. Previous research by Hoetker and Mellewigt (2009) posed this issue by showing how each type of investment entails different hazards of opportunism and requires different governance structures. Our paper complements theirs by also highlighting the importance of taking into account the type of supplier investing in these specific assets.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to consider other mechanisms used to enhance coordination in non-equity alliances, such as teams, administrative interfaces with parents, dedicated alliance staff, reporting mechanisms and procedures, etc. (e.g., Hoetker and Mellewigt, 2009).…”
Section: Contributions and A Research Agendamentioning
confidence: 99%
“…It also appears that while previous literature has made a sharp distinction between formal versus relational governance mechanisms, it would appear that elements of both exist for certain governance mechanisms. For instance, Hoetker and Mellewigt (2009) classify steering committees as one of several relational governance mechanisms as they entail a social component, but as noted in the foregoing discussion, steering committees also have authority that is specified in the contract. As a result, these structures are also an instrument of formal governance, as are joint venture boards, whose authority is derived from ownership and the legal establishment of the business, yet serve as a venue for interactions between executives from parent firms as well as from the joint venture itself.…”
Section: Contributions and A Research Agendamentioning
confidence: 99%
“…Ever since the importance of relationships has been emphasized in IORs, the focus has shifted towards relational governance (Sharma and Pillai, 2003;Vandaele et al, 2007), which has been acknowledged to positively affect IOR performance (e.g., Saxton, 1997;Dyer and Singh, 1998;Zaheer et al, 1998;Johnston et al, 2004;Lavie et al, 2012). For example, trust has been found to positively affect sales growth, market share, competitiveness, and goal achievements (Claro et al, 2003;Ferguson et al, 2005;Griffith and Myers, 2005;Paulraj et al, 2008;Hoetker and Mellewigt, 2009). In contrast, relatively few studies focus on contractual governance (Vandaele et al, 2007) as can be observed in Table 1.…”
Section: Governing Inter-organizational Relationshipsmentioning
confidence: 99%